1) 2x+7 1
2x -6
x -3
2) 4x + 9 > -15
4x > 24
x > 6
3) 2 - x 5
x -3
2 уровень
4) 7х + 9 < 2х - 1
5х < - 10
х < -2
5) 9х - 14 < 4 + 11х
2х > - 18
х > -9
3 уровень
6) 3 - 2(х-1) > 8+ х
3 - 2х +2 > 8 + х
3х < - 3
х < -1
7) 2(3х - 1) - х =< 3(х+4)
6х - 2 - х =< 3х + 12
2х 14
х 7
Пошаговое объяснение:
1) 2x+7 >= 1
2x >= -6
x >= -3
2) 4x + 9 > -15
4x > 24
x > 6
3) 2 - x =< 5
x >= -3
2 уровень
4) 7х + 9 < 2х - 1
5х < - 10
х < -2
5) 9х - 14 < 4 + 11х
2х > - 18
х > -9
3 уровень
6) 3 - 2(х-1) > 8+ х
3 - 2х +2 > 8 + х
3х < - 3
х < -1
7) 2(3х - 1) - х =< 3(х+4)
6х - 2 - х =< 3х + 12
2х =< 14
х =< 7